2010
DOI: 10.1016/j.jcv.2010.06.013
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of viral respiratory tract infections in a prospective cohort of infants and toddlers attending daycare

Abstract: Using molecular techniques, viruses were identified in approximately twice as many RTIs as previously reported in a daycare cohort. Infections with newly identified viruses, such as HMPV and CoV subtypes were less frequent and severe than infections with RSV, AdV and RhV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
107
4
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 111 publications
(125 citation statements)
references
References 23 publications
13
107
4
1
Order By: Relevance
“…Other studies also reported a high percentage of viral infection cases, even though a higher number of viruses were tested in those studies than in ours. 7,25,26 Still, the high frequency of viral infections we detected could reflect the testing for the main viruses responsible for ARI in children and the application of 2 detection methods.…”
Section: Discussionmentioning
confidence: 94%
“…Other studies also reported a high percentage of viral infection cases, even though a higher number of viruses were tested in those studies than in ours. 7,25,26 Still, the high frequency of viral infections we detected could reflect the testing for the main viruses responsible for ARI in children and the application of 2 detection methods.…”
Section: Discussionmentioning
confidence: 94%
“…A history of maternal atopy and asthma also increases the risk of severe rhinovirus infection in the offspring (41). Finally, more frequent exposure to pathogens in settings such as day care leads to increased infection rates of all types of respiratory pathogens (42), and rhinoviruses are more commonly associated with severe outcomes than most other viruses acquired in day care (43).…”
Section: Risk Factors For Severe Rhinovirus Infectionmentioning
confidence: 99%
“…Existen varios estudios en los que se ha demostrado que puede presentarse la coexistencia de estos virus, pudiendo no tener manifestaciones adicionales o presentarse como una enfermedad de mayor seriedad. Se cree que el daño citopático producido por el virus inicial promueve la llegada y el crecimiento de otro virus e incluso bacterias (1,2,6,9). Otro de los pacientes tenía antecedentes de infecciones de las vías respiratorias inferiores asociadas a M. pneumoniae (3,6,7).…”
Section: Discussionunclassified